Hierarchically Nanostructured 1D Conductive Bundle Yarn-Based Triboelectric Nanogenerators - Ko, Won Bae (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.